TREND PENGANGGURAN TERBUKA TERDIDIK DI DAERAH ISTIMEWA YOGYAKARTA - , RISKA ARUMNINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
During 2007 until 2011, the Workforce Participation Level (TPAK) for Junior High School (SMP) educated groups or less had decreased, while TPAK for Senior High School (SMA) educated groups or less had increased. However, during the five years, an opened unemployment from Senior High School educated groups or above (educated-opened unemployment) always higher than Junior High School educated groups or less. Therefore, this research was aimed to know an educated-opened unemployment trend in Yogyakarta Special Region (DIY) and its influencing factor. This was a quantitative research using a secondary data from survey result performed by Statistical Central Bureau (BPS) namely 2007 to 2011 SAKERNAS raw data. Variables used in this research were sex, residence region, age group and highest education of opened unemployment. Data analysis technique used a crosstab. The research result showed that an educated-opened unemployment trend was dominated by males based on a nurture theory by John Stuart Mill it showed that there was a patriarchy ideology dominant in society. A higher urban educated-opened unemployment trend showed that gap between rural and urban was still higher so that job seeker stream from rural to urban. An educated-opened unemployment trend was also dominated by the youth aged 20-24. This showed that the available educational system less able to meet job seekersâ needs. A formal education only yielded âready to knowâ graduates to further being trained to work instead of âready to workâ graduates. Factors influenced an educated-opened unemployment trend dominated by males was a construct that males were main breadwinners in the family, while females were only secondary breadwinners, females also had a multiple burdens if they worked, besides there was still a construct that âfemales natureâ was to work in domestic sectors. Factors influenced an educated-opened unemployment trend dominated in urban was urbanization, modern and formal sectors in urban, and the rural solidarity strength that caused rural people help to each other to look for a job for their relatives. Meanwhile, an educated-opened unemployment trend was dominated by a 20-24 aged groups was influenced by allowance factors from family i.e. monthly fee as well as foods, no responsibility to the family, resources scarcity and social institutional obstacles. This was due to lack of work experience and skills, unsuitability between formal education which produced skills and job seekersâ needs, company policies that needed a lot of requirements and special skills to enter and also a hope to get a high-social status job. Keywords: opened unemployment, educated unemployment.